PENGEFEKTIFAN CDPEMBELAJARAN SKI UNTUK MENINGKATKAN KEPEKAAN APRESIASI BUDAYA PADA PESERTA DIDIK DI MAN BANGIL KABUPATEN PASURUAN - Anshar Prayudhi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2016)
From the learning acquisition side seing, the History of Islamic Cultur-alsubject matter is expected to be able to enrich pupil’s competence as adispo-sition for pupils in establishing and deciding behavior which is thebasic of for their social position in interpersonal interaction. With suchmental attitude, pupils will be able to own appreciation sensitivity ingiving response toward the items of Islamic cultur. This experimentalresearch shows that CD which is used in teach-ing subject matterimproves (75,5%) to pupils’ cultural apresiation skill. It is proved frompupils’ perspective toward cultur items before and after CD usage.